Gender Differences in Visual-Spatial Skills: Myth or Fact? A Systematic Literature Review - Nabilahumaida Nabilahumaida; Nur Siti Maghfira Maulani Nurdin; Sri Kusrohmaniah; Augustina Sulastri (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2024)
This study examines gender differences in visual-spatial abilities, focusing on the consistency of these differences and the factors influencing them. The study aims to understand the extent to which gender differences in visual-spatial abilities are consistent and what factors contribute to these differences. Utilizing a Systematic Literature Review (SLR) approach guided by PRISMA, this study synthesizes findings from various previous studies on visual-spatial abilities in men and women. Literature searches were conducted in Scopus, Web of Science, and Taylor & Francis databases, with inclusion criteria covering empirical studies from the past two decades. The selection process yielded 13 primary studies for thematic analysis. Inductive thematic analysis reveals that gender differences in visual-spatial abilities, consistently favoring men, are supported by differences in brain structure and testosterone levels. However, these findings are not entirely absolute, as training and experience show potential for reducing the gender gap in visual-spatial abilities. Cross-cultural studies also suggest that social and cultural contexts influence visual-spatial abilities, regardless of gender. The findings of this study contribute significantly to the literature on gender differences in visual-spatial abilities by strengthening the understanding of biological, social, and educational factors that impact these differences.